Point-of-care ultrasound for general practitioners: a systematic needs assessment - Thomas Løkkegaard; Tobias Todsen; Leizl Joy Nayahangan; Camilla Aakjaer Andersen; Martin Bach Jensen; Lars Konge (Taylor & Francis Group, 2020)
Objective: The aim of the study was to achieve consensus among a group of ultrasound proficient general practitioners (GPs) from Denmark, Norway, Sweden and Finland on which ultrasound scanning modalities and ultrasound-guided procedures are essential to GPs in their daily work for the purpose of including them in a basic ultrasound curriculum. Design: The Delphi methodology was used to obtain consensus. Subjects: Sixty Scandinavian GPs with more than two years of point-of-care ultrasound (POCUS) experience were invited to join the Delphi expert panel. Main outcome measures: In the first Delphi round each member of the panel was asked to produce a list of scanning modalities and procedures which they found relevant to include in a basic ultrasound curriculum. In Delphi round two, these suggestions were presented to the entire panel who assessed whether they found them essential in their daily work. Items not reaching consensus in round two, were presented to the panel in a third and final round. Items reaching more than 67% agreement were included. Results: Forty-five GPs were included in the study and 41 GPs completed all rounds. Agreement was obtained on 30 scanning modalities and procedures primarily within the musculoskeletal (8), abdominal (5), obstetric (5) and soft tissue (3) diagnostic areas. Four ultrasound-guided procedures were also agreed upon. Conclusion: A prioritized list of 30 scanning modalities and procedures was agreed upon by a group of ultrasound proficient GPs. This list could serve as a guideline when planning future POCUS educational activities for GPs.Key points Point-of-care ultrasound (POCUS) is increasingly being used by general practitioners (GPs), but little is known about which ultrasound applications are most used. We performed a systematic needs assessment among a group of ultrasound proficient GPs using the Delphi methodology for the purpose of establishing a basic POCUS curriculum. The process resulted in a prioritized list of 30 scanning modalities and ultrasound guided procedures. Our study provides the basis for an evidence-based basic POCUS curriculum for GPs.